Cephalometric effects of the use of 10-hour Force Theory for Class II treatment - Cabrera,Marise de Castro (2012)
OBJECTIVE: This study aimed to evaluate the cephalometric effects promoted by the orthodontic treatment of Class II malocclusion patients with the use of the 10-Hour Force Theory, that consists in the use of fixed appliances with 8 hours a day using a cervical headgear appliance and 16 hours a day using Class II elastics, 8 hours on the first mandibular molar and 8 hours in the second mandibular molar. METHODS: Sample comprised 31 patients with mean initial age of 14.90 years, final mean age of 17.25 years and mean treatment time of 2.35 years. The lateral cephalograms in pre-treatment and post-treatment stages were evaluated. Evaluation of cephalometric changes between initial and final treatment phases was performed by paired t test. RESULTS: The cases treated with the 10-Hour Force Theory presented a slight restriction of anterior displacement of the maxilla, increase in the effective length of the mandible, significant improvement of the maxillomandibular relationship, significant increase in anterior lower face height, distal tipping of the maxillary premolar crowns, extrusion and distal tipping of the roots of maxillary molars, significant proclination and protrusion of mandibular incisors, significant extrusion and mesialization of mandibular molars, besides a significant correction of the molar relationship, overjet and overbite. CONCLUSION: The use of the 10-Hour Force Theory in treatment of Class II malocclusion provided satisfactory results.